Fabrication of Functionally Graded Open-cell Aluminium Foam Using Graded NaCl in Infiltration Casting - Arifhakim Azizan, Mohd; Azlina Mohd Salleh, Noor; Hussain Ismail, Muhammad; David Natarajan, Valliyappan (International Journal of Engineering and Technology, 2018)
Functionally graded material (FGM) is a material that has varying composition, porosity and microstructure. Such material is created to achieve a specified function. As for this research, an Aluminium based FGM was fabricated using infiltration-casting method whereby graded NaCl act as the filter and space holder material. The NaCl grain is graded into 2, 3 and 4mm in size. The results showed that the porosity of the Functionally Graded Open Cell Aluminium Foam (FGOCAF) fabricated using infiltration process is highly dependent on the sizes of NaCl grains used. By increasing the size of NaCl grain in infiltration casting method, significantly increase the porosity of the FGOCAF. It can be concluded that the NaCl grain plays an important role to define the functionality-graded structure of the final product whereby the product will show layers of porosity inside it.Â Â